Association between dietary inflammatory index and fecal incontinence in American adults: a cross-sectional study from NHANES 2005–2010 - Li, Zhigang; Chen, Xing; Huang, Jiaobao; Cheng, Fei; Wu, Zhao; Yuan, Lebin; Li, Xiaodong; Shen, Wei (Frontiers in Nutrition, 2024)
Objective Recent studies have demonstrated that the Dietary Inflammatory Index (DII) is relevant to abnormal gut health. However, there is a lack of studies that have explicitly explored the link between fecal incontinence (FI) and DII. The current study aims to explore the relationship between DII and FI. Methods The cross-sectional study enrolled a total of 11,747 participants aged 20–85 from NHANES 2005–2010. Weighted logistic regression was conducted to evaluate the relationship between DII and FI, and restricted cubic spline (RCS) was employed to assess the dose-response relationship between DII and FI. Subgroup analyses were performed according to age, gender, race, and BMI. Result DII levels were found to be significantly higher in patients with FI than in the normal population (p = 0.016). After adjusting for all covariates, DII was found to be significantly correlated with FI (model 2: Q4 vs. Q1, OR = 1.49, 95% CI: 1.04–2.14, p = 0.032, p for trend = 0.039). The dose-response curve revealed that there was no non-linear correlation between DII and FI (p-non-linear = 0.234). Subsequent subgroup analyses uncovered that DII was notably associated with FI in the old (Q4 vs. Q1, OR = 1.84, 95% CI: 1.07–3.18, p = 0.030), female (Q4 vs. Q1: OR = 2.02, 95% CI: 1.23–3.33, p = 0.008), non-Hispanic white (Q4 vs. Q1: OR = 1.70, 95% CI: 1.12–2.59, p = 0.015) populations. Conclusion DII was positively associated with FI, particularly among old, female and non-Hispanic white individuals. Decreasing daily dietary inflammatory levels may be an effective tactic to prevent FI, but the precise mechanisms need to be further investigated.